1993
DOI: 10.1128/jb.175.6.1605-1611.1993
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of lipopolysaccharide O side chains by Pseudomonas aeruginosa PAO1 requires the enzyme phosphomannomutase

Abstract: We have cloned a lipopolysaccharide (LPS) biosynthetic gene from Pseudomonas aeruginosa PAO1 that complements the defect in the production and incorporation of LPS O side chains in the LPS-rough strain AK1012. This gene was characterized by pulsed-field gel electrophoresis, deletion and restriction mapping of the cloned DNA, and biochemical analysis of the protein product. The cloned DNA was found to map to the 7-to-11-min region of the P. aeruginosa chromosome, and the gene needed for complementation of the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
77
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 51 publications
2
77
0
Order By: Relevance
“…GMDH converts GDPmannose into GDPmannuronate, a direct precursor for alginate polymerization (14). The biosynthetic steps preceding GDPmannuronate are shared with lipopolysaccharide biosynthetic pathways and, although necessary for alginate synthesis, are not entirely alginate specific (10,26). In keeping with the pivotal role of GDPmannose dehydrogenase, transcriptional activation of algD is always associated with the mucoid status of P. aeruginosa and represents a committing step towards increased alginate synthesis.…”
mentioning
confidence: 99%
“…GMDH converts GDPmannose into GDPmannuronate, a direct precursor for alginate polymerization (14). The biosynthetic steps preceding GDPmannuronate are shared with lipopolysaccharide biosynthetic pathways and, although necessary for alginate synthesis, are not entirely alginate specific (10,26). In keeping with the pivotal role of GDPmannose dehydrogenase, transcriptional activation of algD is always associated with the mucoid status of P. aeruginosa and represents a committing step towards increased alginate synthesis.…”
mentioning
confidence: 99%
“…Mutants devoid of 0 antigen were considerably more sensitive to serum components and phagocytic effects than their parent strains were. It has been recently demonstrated that the enzyme PMM is involved in LPS synthesis in P. aeruginosa PAO1 (13). Studies with LPS-rough mutant strain AK1012 showed a lack of glucose and rhamnose residues in the LPS and that the probable block in LPS synthesis was in the attachment of glucose or rhamnose residues to the galactosamine in the LPS core (15).…”
mentioning
confidence: 99%
“…Of the thirteen genes required for the biosynthesis and secretion of alginate by P. aeruginosa, twelve are located on the tightly regulated algD operon. The algC gene, located elsewhere in the genome, has additional roles in lipopolysaccharide (LPS) and rhamnolipid biosynthesis (7,8). Biosynthesis of alginate starts with the production of the activated sugar-nucleotide precursor GDP-mannuronic acid from fructose-6-phosphate via the concerted actions of the AlgA, AlgC, and AlgD enzymes (reviewed in ref.…”
mentioning
confidence: 99%